An Analysis of Essential Pediatric Surgical Cases Encountered During a Decade of Large-Scale Military Humanitarian Aid Missions. Issue 11 (30th December 2020) - Gaidry, Alicia D; Lizardo, Radhames E; Prieto, James M; Brill, Jason B; Hernandez, Amy A; Moore, Hope N; Henry, Marion C; Ricca Jr, Robert L; Thangarajah, Hariharan; Bickler, Stephen W; Ignacio, Romeo C
Abstract: Introduction: Disease Control Priorities, 3 rd Edition (DCP3) is an evidence-based, published resource that outlines essential procedures recommended for developing health care systems. These systems must consider various populations and the incidence of certain surgical conditions that require treatment. In relation to pediatric patients, the prevalence of certain surgical conditions encountered remains unclear in several low- and middle-income countries. Over the past 15 years, the USNS Mercy, one of the U.S. Navy's large hospital ships, has led the Pacific Partnership missions, which provide large-scale humanitarian aid throughout Southeast Asia. The data collected during these missions provide an opportunity to analyze the scope of pediatric operations performed in resource-limited countries. This analysis may assist in future planning for specific needs during military humanitarian missions. Materials and Methods: Surgical case data were prospectively collected during the six Pacific Partnership missions from 2006 to 2018. Demographic data were analyzed for all patients ≤8 years of age who underwent an operation. These data were retrospectively reviewed and all case logs were categorized by mission year, procedure-type, and host nation. Operations were classified based on 44 essential operations delineated in DCP3. Primary outcome was incidence of DCP3 essential operations. Secondary outcomes were perioperative complications. Standard statistical methods were performed for descriptive analysis. Results: A total of 3, 209 major and minor operations were performed during 24 port visits in nine countries. Pediatric cases represented 1, 117 (38%) of these procedures. Pediatric surgeons performed 291 (26%) of these cases. Based on DCP3 criteria, 789 pediatric operations (71%) were considered essential procedures. The most common DCP3-aligned procedures were cleft lip repair (432, 57%), hernia repair (207, 27%), and hydrocelectomy (60, 8%). Operative volume for pediatric surgery was highest during the 2008 mission (522 cases), when two pediatric surgeons were deployed, and lowest during the 2018 mission (five cases), when the mission focus was on education rather than surgical procedures and lack of pediatric cases referred by the host nation. Overall complication rate for pediatric cases was 1%. Conclusions: This study represents the largest known analysis of military humanitarian assistance. Pediatric operations represented over one-third of the surgical volume during Pacific Partnership missions from 2006 to 2018. The majority of cases were DCP3-aligned and associated with a low complication rate. Future humanitarian aid missions and host nations should allocate appropriate medical and educational resources to treat DCP3 pediatric surgical diseases in low- and middle-income countries to support long-term capacity building while maintaining optimal surgical outcomes.